Understanding Formal Responses to Intimate Partner Violence and Women’s Resistance Processes: A Scoping Review - Osborn, Max; Rajah, Valli (Trauma, violence & abuse, 2022)
Intimate partner violence (IPV) literature addresses the ways in which women oppose violent male partners through acts of “everyday resistance.” There is a limited understanding, however, of the relationship between women’s resistance and their formal help-seeking in the context of IPV. Our scoping review, which includes 74 articles published in English-language journals between 1994 and 2017, attempts to help fill this gap by developing systematic knowledge regarding the following research questions: (1) How are formal institutional responses discussed within the literature on resistance to IPV? (2) How does institutional help-seeking facilitate or obstruct IPV survivors’ personal efforts to resist violence? We find that institutions and organizations succeed in facilitating resistance processes when they counter victim-blaming ideas and provide IPV survivors with shared community and a sense of control over their futures. However, they fall short in terms of helping survivors by expecting survivors to adhere to a rigid narrative about appropriate responses to violence, devoting insufficient attention to individual-level factors impacting survivors’ vulnerability and ability to access help, and replicating abuse dynamics when interacting with survivors. Policy and practice implications are discussed.